2012
DOI: 10.1007/s00381-012-1900-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of split cord malformation by ultrasound and fetal magnetic resonance imaging: case report and review of the literature

Abstract: An 18-year-old woman with no obstetrics risk factor was referred for routine US screening. At sagittal section, fetal spine was seen to be disordered. A coronal view of the spinal canal showed evidence of widening at the lower thoracic and lumbar level. An echogenic mass was identified within the enlarged spinal canal at level of T6-L5. Fetal MRI and AF-AChE analysis confirmed diagnosis and ruled out other anomalies and spina bifida. Neurological examination of the baby at 16 months of age was normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Because type II diastematomyelia is accounted for in only 22.9% of prenatal diagnoses, we can see that prenatal ultrasound in the diagnosis of type II diastematomyelia still has some difficulties. In the second case of type II diastematomyelia reported in our study, the extra‐intraspinal echo was not clear, and fetal MRI also failed to provide any additional information as a result of the low resolution, which is consistent with a previous report; it may be misdiagnosis if not combined with other characteristics of diastematomyelia. With the increasing resolution of ultrasonography, Blondiaux et al suggested that high‐frequency probes may accurately display the spinal cord of the fetus in mid‐ to late pregnancy, and increase the rate of diagnosing spinal cord defects, especially when the abdominal wall of the mother is thin and close to the fetal spine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because type II diastematomyelia is accounted for in only 22.9% of prenatal diagnoses, we can see that prenatal ultrasound in the diagnosis of type II diastematomyelia still has some difficulties. In the second case of type II diastematomyelia reported in our study, the extra‐intraspinal echo was not clear, and fetal MRI also failed to provide any additional information as a result of the low resolution, which is consistent with a previous report; it may be misdiagnosis if not combined with other characteristics of diastematomyelia. With the increasing resolution of ultrasonography, Blondiaux et al suggested that high‐frequency probes may accurately display the spinal cord of the fetus in mid‐ to late pregnancy, and increase the rate of diagnosing spinal cord defects, especially when the abdominal wall of the mother is thin and close to the fetal spine.…”
Section: Discussionsupporting
confidence: 88%
“…Ultrasonic waves can pass through the spinal canal as a result of incomplete ossification of the fetal spinous lamina, and detect the structure of the spine; thus, they can be used as a method for the early diagnosis of spinal and spinal cord deformities. Since Williams first diagnosed diastematomyelia using ultrasonography in 1985, a total of 44 cases of diastematomyelia have been successfully diagnosed with prenatal ultrasonography, including the four cases reported in the present study. We conducted a retrospective analysis of all 44 cases, and the clinical characteristics can be summarized as follows: Gravidas with diastematomyelia diagnosed prenatally were between the ages of 18 and 40 (mean age, 27.0 ± 5.4 years); the diagnosis of diastematomyelia was confirmed at a gestational age of 13 to 36 weeks (average, 21.8 ± 5.5 weeks); of the 44 cases, 19 (43.2%) occurred at the lumbar level, followed by 11 at the thoracolumbar level (25.0%), 10 at the thoracic level (22.7%), 3 involving the thoracic and lumbar spine (6.8%), and 1 at the sacral spine (2.3%); 27 of 35 cases (77.1%) were categorized as type I diastematomyelia, and 9 of 35 (22.9%) were type II diastematomyelia; and 9 of 44 gravidas (20.5%) were on medications during pregnancy.…”
Section: Discussionmentioning
confidence: 83%
“…Amniotic fluid acetylcholine esterase (AF-AChE) levels and foetal magnetic resonance imaging (MRI) can be helpful to rule out additional anomalies. 4…”
Section: Introductionmentioning
confidence: 99%